Evaluating Dynamic Performance: The Influence of Salient Gestalt Characteristics on Performance Ratings - REB, Jochen (Institutional Knowledge at Singapore Management University, 2007)
It is well recognized that performance changes over time. However, the effect of these changes on overall assessments of performance is largely unknown. In a laboratory experiment, we examined the influence of salient Gestalt characteristics of a dynamic performance profile on supervisory ratings. We manipulated performance trend (flat, linear-improving, linear-deteriorating, U-shaped, and ∩-shaped), performance variation (small, large), and performance mean (negative, zero, positive) within subjects and display format (graphic, tabular) between subjects. Participants received and evaluated information about the weekly performance of different employees over a simulated 26-week period. Results showed strong main effects on performance ratings of both performance mean and performance trend, as well as interactions with display format. Theoretical and practical implications of the results are discussed.